Preparation and characterization of a novel green tea essential oil nanoemulsion and its antifungal mechanism of action against Magnaporthae oryzae - Anand Babu Perumal; Xiaoli Li; Zhenzhu Su; Yong He (Ultrasonics Sonochemistry, 2021)
Blast is one of the most devastating fungal diseases of rice caused by Magnaporthe oryzae. Plant essential oil (EO) can function as antifungal agents and are regarded as a safe and acceptable method for plant disease control. However, EOs are unstable and hydrophobic, which limits its use. In the present study, we aimed for the preparation and characterization of a nanoemulsion (NE) from green tea essential oil (GTO) by ultrasonication method and determined the antifungal activity of NE on M. oryzae. The particle size and zeta potential of the NE were 86.98 nm and −15.1 mV, respectively. The chemical composition and functional groups of GTO and NE were studied by using GC–MS analysis, portable Raman spectroscopy, and FTIR coupled with chemometric analysis. GC–MS analysis showed the major components in GTO and NE were n-Hexyl cinnamaldehyde and L-α-Terpineol. Both GTO and NE showed good antioxidant activity and total phenol content. Moreover, the NE showed good antifungal activity against M. oryzae which was further confirmed by scanning electron microscopy (SEM) examination. Also, confocal Raman micro-spectroscopy (CRM) revealed the antifungal mechanism of GTO and NE on M. oryzae which proves the cell damage. To the best of our knowledge, this is the first study on the antifungal activity of GTO and NE against M. oryzae and also the use of CRM for the evaluation of the chemical changes in single fungal hyphae in a holistic approach. This study suggests that the prepared NE could be a potential candidate for use as a substitute for synthetic fungicides.